Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.2147/jhl.s431157
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Belonging of Women Healthcare Professionals Relates to Likelihood of Leaving

Judith Schaechter,
Richard Goldstein,
Ross Zafonte
et al.

Abstract: Purpose There is a high rate of attrition of professionals from healthcare institutions, which threatens the economic viability of these institutions and the quality of care they provide to patients. Women professionals face particular challenges that may lower their sense of belonging in the healthcare workplace. We sought to test the hypothesis that workplace belonging of women healthcare professionals relates to the likelihood that they expect to leave their institution. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Structural sexism means women often face barriers to returning to work after giving birth, including inadequate leave, lack of private spaces for breast feeding or expressing breast milk, and productivity based pay reductions. Conversely, women’s belief that they can thrive professionally6 is a key component of belonging that can promote retention in the healthcare workforce.…”
Section: Creating Belongingmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural sexism means women often face barriers to returning to work after giving birth, including inadequate leave, lack of private spaces for breast feeding or expressing breast milk, and productivity based pay reductions. Conversely, women’s belief that they can thrive professionally6 is a key component of belonging that can promote retention in the healthcare workforce.…”
Section: Creating Belongingmentioning
confidence: 99%
“…Organisational cultures, policies, and practices should support individuals to improve their sense of belonging. Effective communication of all workplace policies, practices, and accountability measures relating to belonging is vital to ensure all employees are receptive 6789. To reduce attrition from the workforce, these policies and practices must be designed by clinicians from historically under-represented groups (including women, and especially Black women) then operationalised by healthcare organisations in partnership with all employees 816.…”
Section: Creating Belongingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially important for previously excluded and minoritised groups. Although there is a need for more research on the effect of belonging on workforce retention, one recent study showed that greater workplace belonging was found to be significantly related to a reduced likelihood of women in medicine reporting that they intended to leave their institution within the next 2 years [18]. `troublemaker´felt anxious about re-entry´´ [2].…”
Section: Attrition Push Factors: Pathway To a Physician Leaving Organ...mentioning
confidence: 99%
“…It has been demonstrated that as individuals identify more belonging factors in the workplace, the likelihood to leave their current employment decreases (Figure 1). 4 When reviewing feedback from participants of a women's leadership course (99% women, 63% clinicians), 61% of respondents reported a likelihood of leaving their institution within 2 years. An inability to thrive professionally at one's institution was most predictive of attrition.…”
mentioning
confidence: 99%